A Convergent Self-Evaluation Model Madrasah Aliyah Teacher Personality in Character Education in Yogyakarta, Indonesia - Lukman Ahmad Irfan; Hajar Dewantoro; Hanif Cahyo Adi Kistoro; Adzkia Hulwia Hasanah (Universitas Negeri Yogyakarta, 2026)
Personality competence is a crucial aspect in supporting teachers’ effectiveness in learning. This study aims to examine the evaluation of teachers’ personality competence using a qualitative phenomenological approach. Six teachers were selected through purposive sampling, and data were collected through guided interviews using structured protocols. Data analysis involved verbatim transcription, data reduction, data display, and interpretative conclusion drawing. The findings reveal two main dimensions in evaluating teacher personality competence: internal and external factors. Internal factors include the ability to demonstrate noble character, act as a role model, and uphold responsibility, while external factors relate to accountability in religious, social, and cultural domains, as well as adherence to professional ethics. These findings provide a foundational reference for developing a more comprehensive and convergent model of teacher personality competence evaluation in future research.